Phenotypic characterization of regional human meniscus progenitor cells - Wang, Jingsong; Roberts, Sally; Li, Weiping; Wright, Karina (Frontiers in Bioengineering and Biotechnology, 2022)
Stimulating meniscus regeneration using meniscal progenitor cells has been suggested as a promising new strategy. However, there is a lack of studies which decisively identify and characterize progenitor cell populations in human meniscus tissues. In this study, donor-matched progenitor cells were isolated via selective fibronectin adhesion from the avascular and vascular regions of the meniscus and chondroprogenitors from articular cartilage (n=5). The mixed populations of cells from these regions were obtained by standard isolation techniques for comparison. The colony formation efficacy of avascular progenitors, vascular progenitors and chondroprogenitors was monitored using Cell-IQ® live cell imaging. Proliferation rates of progenitors were compared with their mixed population counterparts. Cell surface markers indicative of mesenchymal stromal cells profile and progenitor markers were characterized by flow cytometry in all populations. The fibrochondrogenic capacity was assessed via fibrochondrogenic differentiation and measuring GAG/DNA content and morphology. All meniscal progenitor and chondroprogenitor populations showed superior colony forming efficacy and faster proliferation rates compare to their mixed populations. Progenitor populations showed significantly higher positivity for CD49b and CD49c compared to their mixed population counterparts and chondroprogenitors had a higher positivity level of CD166 compared to mixed chondrocytes. GAG/DNA analysis demonstrated that progenitor cells generally produced more GAG than mixed populations. Our study demonstrates that the human meniscus contains meniscal progenitor populations in both the avascular and vascular regions. Meniscal progenitors derived from the vascular region exhibit enhanced proliferative and fibrochondrogenic characteristics compared to those from the avascular region; this may associate with the enhanced meniscal healing potential in the vascular region. These findings build on the body of evidence which suggests that meniscal progenitors represent an attractive cell therapy strategy for meniscal regeneration.